The lawn : a history of an American obsession - Jenkins, Virginia Scott (Smithsonian Institution Press, 1994)
Lawns now blanket thirty million acres of the United States, but until the late nineteenth century few Americans had any desire for a front lawn, much less access to seeds for growing one. In her comprehensive history of this uniquely American obsession, Virginia Scott Jenkins traces the origin of the front lawn aesthetic, the development of the lawn-care industry, its environmental impact, and modern as well as historic alternatives to lawn mania.